Efektivitas Mediasi Pertanahan dalam Penyelesaian Sengketa Tanah di Luar Pengadilan - Nicky Alyamonica; Seila Beuty Brilliant; Nuha Ayu Nabilah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the effectiveness of land mediation as an out-of-court dispute resolution mechanism facilitated by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency. The research is grounded in the high incidence of land conflicts that often generate legal uncertainty, high costs, and social tension when resolved through litigation. Using a normative legal approach, this study analyzes the relevant regulatory framework, including Law Number 5 of 1960 on Basic Agrarian Principles, Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution, and Ministerial Regulation of ATR/BPN Number 21 of 2020 on Handling and Settlement of Land Cases. The findings indicate that mediation provides a participatory dialogue space, encourages voluntary agreements, and helps preserve social relations among disputing parties. Compared to litigation, mediation is more efficient in terms of time and cost and allows context-sensitive solutions tailored to the parties’ needs. However, its effectiveness is influenced by mediator competence, bargaining balance, and the parties’ legal awareness. Strengthening mediator capacity and improving public understanding of mediation procedures are essential recommendations to enhance mediation’s role in delivering legal certainty and substantive justice in land dispute resolution in Indonesia.